Practices of local governments on traffic signalization of intersections. - Amistad, Franklyn T.
This paper presents the practices of local government units outside Metro Manila on traffic signalization of unsignalized intersections. The information revealed in this research is based on the perspectives of the local officials of the 23 cities or 23.46 percent of the 98 cities in the Philippines excluding the 14 cities of Metro Manila. Most of the city respondents are thickly populated. Majority of them are first class cities wherein there is a yearly increase in the number of registered motor vehicles. The level of necessity and level of attainment of objectives for traffic signalization are Very High and High, respectively. Some of the LGUs have not installed traffic signals because of budget constraints. They tap the expertise of the Traffic Engineering Center (TEC), Traffic Engineering and Management (TEAM), and the academe (e.g. National Center for Transportation Studies) for the conduct of traffic engineering studies. TEC warrant is the most frequently used criterion considering vehicular volume as the indicator for the warrants. There is a significant relationship between the basis in warranting signalization for intersection and the level of necessity and level of attainment of objectives, between funding agencies and level of necessity and level of attainment of objective; objectives. Also there is a significant relationship between the consultation which was administered by local officials and the level of attainment of objectives for signalization. The formulation of the guidelines in the implementation of traffic signalization among the local government units and agencies concerned are recommended.
Keywords: Traffic Signalization; Traffic Management